The current surgical management of refractory full-thickness macular holes. (2nd January 2022) - Caporossi, Tomaso; Ripa, Matteo; Governatori, Lorenzo; Scampoli, Alessandra; Gambini, Gloria; Rizzo, Clara; Kilian, Raphael; Rizzo, Stanislao
ABSTRACT: Introduction: Despite the great advancements in full-thickness macular hole (FTMH)-surgery that we have witnessed in the last decade, refractory FTMHs still occur. Areas covered: Refractory FTMHs may result from the clinical characteristics and conformation of the hole, or from poor intraoperative and postoperative management. Failure of pars plana vitrectomy (PPV) and internal limiting membrane (ILM) peeling represents a challenge for vitreoretinal surgeons, and the continuous proposal of new surgical techniques expresses the ongoing need for the optimal treatment of macular holes. We review the current management and surgical techniques for refractory macular holes, highlighting evidence from recent studies. Expert opinion: Surgical techniques continue to improve in order to satisfy the demands for the best management of refractory macular holes.